“Earnings Quality and Trading Volume Reactions Around Earnings Announcements: International Evidence” (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This paper challenges the widely held assumption in financial modeling that market participants interpret public information identically. This study aims to investigate the relationship between earnings quality and trading volume reactions around earnings announcements across a diverse range of international markets. By analyzing the relationship between trading volume and stock returns around public announcements, we find evidence inconsistent with this assumption. To address this inconsistency, they develop a novel model of trade incorporating differential interpretations, which aligns with the observed volume-return relation.